PENGARUH PENDIDIKAN FORMAL DAN PELATIHAN TERHADAP KINERJA AMIL ZAKAT DI KOTA KENDARI (Studi pada Kecamatan Puwatu, Kecamatan Wawombalata dan Kecamatan Abeli di kota kendari) - Wahyuniati Wahyuniati; Hamid Hamid (IQTISHODUNA, 2017)
This research aims to know the effect of formal education and training toward the performance ofAmil Zakat in Kendari. The data collecting method used questionnare. The Sample consisted of 44 respondents.Based on the result of statistic analyst test found that there were an effect of the formal education and trainingtoward the performance of Amil Zakat in Kendari while the simultaneous test result used Ftest 92,892 and Fsig0,000  = 0,05. In other words, Formal Education (X1) which are religion education and general education,and Training (X2) which the material are execution time, and tutor, simultaneously have significant effecttoward the performance of Amil Zakat (Y) on trusty level 95%.